Methanol oxidation on the PtPd(111) alloy surface: A density functional theory study. Issue 3 (20th September 2017) - Xu, Jing; Guo, Sheng; Hou, Fei; Li, Jing; Zhao, Lianming
Abstract: The mechanisms of methanol (CH3 OH) oxidation on the PtPd(111) alloy surface were systematically investigated by using density functional theory calculations. The energies of all the involved species were analyzed. The results indicated that with the removal of H atoms from adsorbates on PtPd(111) surface, the adsorption energies of (i) CH3 OH, CH2 OH, CHOH, and COH increased linearly, while those of (ii) CH3 OH, CH3 O, CH2 O, CHO, and CO exhibited odd‐even oscillation. On PtPd(111) surface, CH3 OH underwent the preferred initial CH bond scission followed by successive dehydrogenation and then CHO oxidation, that is, CH3 OH → CH2 OH → CHOH → CHO → CHOOH → COOH → CO2 . Importantly, the rate‐determining step of CH3 OH oxidation was found to switch from CO → CO2 on Pt(111) to COOH → CO2 + H on PtPd(111) with a lower energy barrier of 0.96 eV. Moreover, water also decomposed into OH more easily on PtPd(111) than on Pt(111). The calculated results indicate that alloying Pt with Pd could efficiently improve its catalytic performance for CH3 OH oxidation through altering the primary pathways from the CO path on pure Pt to the non‐CO path on PtPd(111). Abstract : The mechanisms of methanol oxidation on the PtPd(111) alloy surface are systematically evaluated by means of density functional theory calculations. The reaction prefers a path in which the initial CH bond scission step is followed by successive dehydrogenation and CHO oxidation. The simulation results suggest that alloying Pt with Pd efficiently improves catalytic performances for CH3 OH oxidation through altering the primary pathways from the CO path on pure Pt to a non‐CO path.